INFORMATIVE EVALUATIONS OF THE VALUE OF THE O2/CO2 RATIO IN THE PHYSIOLOGY OF BREATHING - Mintser, O. P.; Shchukin, V. S. (Medical Informatics and Engineering, 2023)
Background. The article, based on the analysis of known facts related to the physiology of human breathing, suggests the existence of a new group of physiological constants related to the estimation of the О2/СО2 ratio during gas exchange. Considering this ratio as an important constant of homeostasis allows us to draw some conclusions that may be of practical importance. The aim of the study. Discussion of the possibility of recognizing the ratio О2/СО2 ~ 1 as a physiological constant of homeostasis of the human body, Materials and methods. Results. The article consists of three messages. In the first, the facts of the physiology of breathing are given, the meaning and contradictions of the respiratory coefficient and dead space are analyzed, and the necessary provisions of the physiology of breathing are considered. In the second message, the necessary provisions of gas analysis are given, and, finally, in the third, the possibility of extracting new physiological constants is analyzed. Conclusions. Preliminary conclusions have been drawn on the first report. 1. Between "taking into account (as a null hypothesis)" the fact of the existence of the ratio О2/СО2 ~ 1 and recognizing it as a constant of homeostasis, there is a long distance, on which the conclusions that logically and reasonably follow from the fact of recognizing the existence of a new physiological constant are "located". 2. Consideration of the use of the ratio pO2 ~ pCO2 can provide a new approach to a more complete understanding of the risk of chronic diseases, behavioral strategies to ensure a healthy lifestyle, in particular, understanding in which a person relies on fats, carbohydrates or proteins for energy, and for specialists - an idea about the physiology of gas exchange and the peculiarities of metabolism, which were not previously studied in the epidemiology of chronic diseases.